Analyzing Theme and Rheme in the Urdu Translation of the Documentary Living Without Water - Walees Fatima (Journal of Peace, Development and Communication, 2024)
This research examines thematic expressions using theme-rheme analysis of the English documentary 'Living Without Water' as a descriptive examination of textual metafunction. The translation is conducted by a researcher with a communication approach, focusing on the subject matter and the conveyance of information, namely the theme and rhyme. The emphasis is on meaning in the translation of text from English to Urdu, as Halliday and Hasan examine the principles of text connection via the concept of textual metafunction (Al-Azzawi, 2004). Thematic expressions are examined as Theme and Rheme, using various samples from the data, which indicate distinct alterations and transitions in theme and rheme. The deficiency of understanding obscures the message of translated documentaries from English to Urdu. The concept of Theme Rheme is examined in the target book, and the translator encountered some literary challenges.